Influencer Marketing Impact on Consumer Behavior: Trust, Authenticity, and Brand Engagement in Social Media - Chavda, Kishan; Chauhan, Rahul (Indonesian Journal Publisher, 2024)
This abstract summarizes recent research on the influence of social media influencers on consumer behavior. Three key studies are highlighted: one exploring the impact of different categories of female social media influencers on consumer credibility and purchase intention, another investigating the psychological mechanisms underlying influencer marketing, and a third examining the moderating role of cultural factors on influencer-consumer relationships. The studies emphasize the multifaceted nature of influencer marketing and underscore the importance of considering influencer types, psychological processes, and cultural differences in designing effective marketing strategies. Themes such as influencer credibility, psychological mechanisms, and cultural moderation emerge as significant factors shaping consumer behavior in the digital age.